Life stages, growth, and habitat suitability of Clupeiformes in Biru Bay, Bali Strait: Stadia hidup, pertumbuhan, dan kesesuaian habitat Clupeiformesdi Teluk Biru, Selat Bali - Nazal, Muhammad Faris; Simanjuntak, Charles Parningotan Haratua; Kurniawan, Fery; Lumban-Gaol, Jonson (Habitus Aquatica, 2026)
Biru Bay, a lift-net fishing ground in the Bali Strait, plays a key role in supporting Clupeiformes fishery production in Muncar and the surrounding Bali Strait region. This study aims to evaluate the species composition and growth patterns of Clupeiformes caught in Biru Bay and their relationship with environmental parameters. Sampling was conducted during the northwest monsoon (December 2023, February 2024) and the first transitional season (March–April 2024). Data analyses included assessments of species composition, length-weight relationships, condition factors, spatiotemporal variability of oceanographic parameters, and Canonical Correspondence Analysis. Clupeiformes catches during both seasons consisted of six species, with monthly variation in predominant species. Most of the individuals were juvenile fish, with the exception of Spratelloides delicatulus, which was frequently found in both juvenile and adult stages. The majority of species exhibited positive allometric growth and were in good condition (CF > 1.00). Physicochemical parameters varied over time, supporting the presence of fish in this area. Chlorophyll-a levels decreased during the northwest monsoon but increased before the transitional season, showing an inverse pattern to sea surface temperature. Four key environmental parameters—temperature, salinity, dissolved oxygen, and chlorophyll-a—were significantly associated with the composition of Clupeiformes.